Genetic Diversity of Human Immunodeficiency Virus Type 1 in Asymptomatic Blood Donors in Islamabad, Pakistan - Waheed, Usman; Noor, Farooq Ahmed; Saba, Noore; Wazeer, Akhlaaq; Qasim, Zahida; Arshad, Muhammad; Karimi, Saira; Farooq, Ahmad; Usman, Javaid; Zaheer, Hasan Abbas (Journal of Laboratory Physicians, 2020)
Objective The serological testing of human immunodeficiency virus (HIV) is mandatory under the blood safety legislation of Pakistan; hence, data exist on the prevalence of HIV in blood donors. However, little is known about the molecular epidemiology of HIV in the blood donor population. Therefore, the current study was designed to study the genetic diversity of HIV-1 infection in a population of apparently healthy treatment-naive blood donors in Islamabad, Pakistan.Material and Methods A total of 85,736 blood donors were tested for HIV by the chemiluminescence immunoassay. All positive donor samples were analyzed for the presence of various HIV genotypes (types and subtypes). Viral ribonucleic acid was extracted from blood samples of HIV positive donors and reverse transcribed into complementary deoxyribonucleic acid (cDNA). The cDNA of all positive donors was then analyzed for the presence of various HIV genotypes (types and subtypes) by employing subtype-specific primers in a nested polymerase chain reaction. The amplified products were run on ethidium bromide-stained 2% agarose gel and visualized using a ultraviolet transilluminator. A particular subtype was assigned to a sample if the subtype-specific reaction made a band 20% highly intense compared with the band made by the subtype-independent reaction.Results A total of 85,736 blood donors were screened for the presence of antibodies to HIV. Out of them, 114 were initially found reactive for HIV. The repeat testing resulted in 112 (0.13%) positive donors, 95% confidence interval 0.0014 (0.0011–0.0018). These 112 samples were analyzed for molecular typing of HIV-1. The predominant HIV-1 subtype was A (n = 101) (90.1%) followed by subtype B (n = 11) (9.9%).Conclusion These findings are key to understand the diversified HIV epidemic at the molecular level and should assist public health workers in implementing measures to lessen the further dissemination of these viruses in the country.
Keywords: HIV; AIDS; blood; donors; genotypes; epidemiology